Pembenahan Greenhouse sebagai Upaya Peningkatan Fasilitas Edukasi Lingkungan: Greenhouse Improvement as an Effort to Improve Environmental Education Facilities - Misrawati Misrawati; Mirsa Marjelita; Januatri Januatri; Risna Suryani (Pengabdian Pendidikan Indonesia, 2026)
This study aims to comprehensively describe the process and outcomes of greenhouse renovation through teaching assistance (KKN) activities to improve the quality of agricultural educational facilities in schools and communities. The activity began with an observation of the greenhouse's initial condition, which revealed various problems, including a rusty, weak frame, torn UV plastic that did not adequately protect the plants, a malfunctioning irrigation system, and a declining growing medium. Based on these findings, collaborative improvement steps were taken involving students, teachers, and the local community. Improvement activities included strengthening and repairing the greenhouse structure, replacing the UV plastic, revitalizing the drip irrigation system to improve efficiency, and updating the growing medium with more productive organic materials. In addition, the greenhouse was also integrated as a project-based learning medium to improve students' scientific literacy, practical skills, and environmental awareness. The results showed that this improvement program was successful not only in improving the greenhouse's physical condition but also in significantly increasing plant productivity. Furthermore, this activity also enriched the students' learning experience through hands-on practice and strengthened active community participation in the management of agricultural facilities. Overall, this program can create a more effective, contextual, and sustainable learning environment at the school and village levels and deliver positive socio-economic impacts.